Serodiagnosis of leptospiral infections using recombinant LipL32 antigen boud carboxyl-modified latex beads - KUMAR, T MASENTHIL; SUBATHRA, M; DASS, P RAMA (The Indian Journal of Animal Sciences, 2011)
The recombinant outer membrane protein antigen based LAT was evaluated with suspected cattle and dog sera. The rLipL32 was specific for pathogenic serovars of Leptospira. Relative sensitivity and specificity of LAT was 94.84% and 96.55% for dog sera and 93.68% and 98.3% for bovine sera, respectively. The test was simple, rapid and cost effective for large scale screening of bovine and dog sera against leptospiral antibodies.Â